(v-3)(v-6)=0

Simple and best practice solution for (v-3)(v-6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (v-3)(v-6)=0 equation:


Simplifying
(v + -3)(v + -6) = 0

Reorder the terms:
(-3 + v)(v + -6) = 0

Reorder the terms:
(-3 + v)(-6 + v) = 0

Multiply (-3 + v) * (-6 + v)
(-3(-6 + v) + v(-6 + v)) = 0
((-6 * -3 + v * -3) + v(-6 + v)) = 0
((18 + -3v) + v(-6 + v)) = 0
(18 + -3v + (-6 * v + v * v)) = 0
(18 + -3v + (-6v + v2)) = 0

Combine like terms: -3v + -6v = -9v
(18 + -9v + v2) = 0

Solving
18 + -9v + v2 = 0

Solving for variable 'v'.

Factor a trinomial.
(3 + -1v)(6 + -1v) = 0

Subproblem 1

Set the factor '(3 + -1v)' equal to zero and attempt to solve: Simplifying 3 + -1v = 0 Solving 3 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1v = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1v = 0 + -3 -1v = 0 + -3 Combine like terms: 0 + -3 = -3 -1v = -3 Divide each side by '-1'. v = 3 Simplifying v = 3

Subproblem 2

Set the factor '(6 + -1v)' equal to zero and attempt to solve: Simplifying 6 + -1v = 0 Solving 6 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1v = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1v = 0 + -6 -1v = 0 + -6 Combine like terms: 0 + -6 = -6 -1v = -6 Divide each side by '-1'. v = 6 Simplifying v = 6

Solution

v = {3, 6}

See similar equations:

| 2sin(3x)+2sin(x)=0 | | 6s^2-5st+t^2=0 | | Y=8x-100 | | 5n^2-6=-94 | | 100/x=20 | | 3(1-3a)= | | 2-x=5x+4 | | 26-7/8x=2 | | -8x^2+46x+30=0 | | -5(w+7)(-w+2)=0 | | 4x+20=56 | | 48+20=56 | | 3(2x+1)=5x+3 | | (185-2x)+(x-20)=90 | | 4(5-3x)=44 | | 6(-10b+10)= | | X+3-2x=x-7 | | 2(x+3)-13=26+24-1 | | 0=-5/2x-2 | | 16x^2+40x+5=0 | | 16x-15=30x+11 | | 150/x=10 | | 2-2*2+2=0 | | 3squared+4=27 | | 3x+6y=350 | | -0.4w=-3 | | 6m+3=-15+2m | | 540/x=90 | | 16=JohnCENA | | -26=-7+9(b+8) | | -y^2+6y+x-9=0 | | 99=33x+9x+15 |

Equations solver categories